Escalamiento de modelos cinéticos para evaluar procesos de inyección de aire en yacimientos de crudo pesado en un campo X de Ecopetrol S.A. (2014)
The present investigation studies the effects of upscaling and downscaling in a combustion tube model (changes in cells number.) The goal is to observe if the changes have an impact in rate production, cumulated production, among other variables. Based on the observations we will obtain a numeric adjustment or a general solution for realizable changes that occur in the base model, these changes are based on radial and vertical cells. This is focused to the possibility to reproduce the laboratory models to a field scale.